The economics of the democratic deficit: the effect of IMF programs on inequality - Lang, Valentin (Discussion paper series, 2016)
This study investigates the distributional effects of international organizations within their member countries. It addresses the issue empirically by examining the causal effect of International Monetary Fund (IMF) programs on income inequality. Introducing a new instrumental variable for IMF programs, I exploit time variation in the IMF’s liquidity and cross-sectional variation in a country’s probability of having a lending arrangement with the IMF. Using panel data for 155 countries over the 1973–2013 period, the results show that IMF programs substantially increase income inequality in democracies, while having no such effect in non-democracies. The size of this effect on democracies is smaller the more democratized the IMF’s decision-making processes are. These results are consistent with the theory that powerful, ‘democratically deficient’ international organizations that interfere in domestic politics are capable of restricting the responsiveness of democratic governments to the preferences of their citizens.
Gesehen am 07.12.2016
Keywords: Arbeitspapier; Graue Literatur